Comparison of different histological indexes in the assessment of UC activity and their accuracy regarding endoscopic outcomes and faecal calprotectin levels. Issue 4 (3rd February 2018) - Magro, Fernando; Lopes, Joanne; Borralho, Paula; Lopes, Susana; Coelho, Rosa; Cotter, José; Castro, Francisca Dias de; Sousa, Helena Tavares de; Salgado, Marta; Andrade, Patrícia; Vieira, Ana Isabel; Figueiredo, Pedro; et al.
Abstract : Objective: Histological remission is being increasingly acknowledged as a therapeutic endpoint in patients with UC. The work hereafter described aimed to evaluate the concordance between three histological classification systems—Geboes Score (GS), Nancy Index (NI) and RobartsHistopathologyIndex (RHI), as well as to evaluate their association with the endoscopic outcomes and the faecal calprotectin (FC) levels. Design: Biopsy samples from 377 patients with UC were blindly evaluated using GS, NI and RHI. The results were compared with the patients' Mayo Endoscopic Score and FC levels. Result: GS, NI and RHI have a good concordance concerning the distinction between patients in histological remission or activity. RHI was particularly close to NI, with 100% of all patients classified as being in remission with NI being identified as such with RHI and 100% of all patients classified as having activity with RHI being identified as such with NI. These scores could also predict the Mayo Endoscopic Score and the FC levels, with their sensitivity and specificity levels depending on the chosen cut-offs. Moreover, higher FC levels were statistically associated with the presence of neutrophils in the epithelium, as well as with ulceration or erosion of the intestinal mucosa. Conclusions: GS, NI and RHI histopathological scoring systems are comparable in what concerns patients' stratification into histological remission/activity. Additionally, FC levels are increased when neutrophils are present in the epithelium and the intestinal mucosa has erosions or ulcers. The presence of neutrophils in the epithelium is, indeed, the main marker of histological activity.